2011
DOI: 10.1007/s10461-011-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

‘A Virus and Nothing Else’: the Effect of ART on HIV-Related Stigma in Rural South Africa

Abstract: While the World Health Organization acknowledges the potential of antiretroviral therapy to reduce HIV-related stigma, few studies examine the nature of this linkage. This article discusses the connection between ART and HIV-related stigma, using qualitative analysis of interviews with HIV-positive adults at a rural South African clinic. The data has two main implications for ART's role in stigma reduction: it strengthens the plausibility that ART can reduce stigma through weakening HIV/AIDS's link with disfig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 9 publications
(6 reference statements)
6
36
1
Order By: Relevance
“…Another explanation could be that many who reported that they did not test as part of the HCT campaign actually did in fact test as part of the HCT campaign but might not have been aware of their participation. ART use was also not found to be associated with HIV seropositive status disclosure in the present paper, again conflicting with previous studies ( [40,54] vs. [8,56]). This could be because some PLHIV on ART may think that since they are taking their medications they are healthy and not infectious due to ARVs decreasing their viral load, and therefore do not feel the need to disclose their status.…”
Section: Discussioncontrasting
confidence: 99%
“…Another explanation could be that many who reported that they did not test as part of the HCT campaign actually did in fact test as part of the HCT campaign but might not have been aware of their participation. ART use was also not found to be associated with HIV seropositive status disclosure in the present paper, again conflicting with previous studies ( [40,54] vs. [8,56]). This could be because some PLHIV on ART may think that since they are taking their medications they are healthy and not infectious due to ARVs decreasing their viral load, and therefore do not feel the need to disclose their status.…”
Section: Discussioncontrasting
confidence: 99%
“…The high reported levels of HIVrelated communication are encouraging and suggest the normalisation of HIV (Zuch & Lurie, 2012). Consistent with previous published research, we observed higher levels of MPI among participants who reported higher levels of communication with partners (Ditekemena et al, 2012;Kalembo et al, 2012;Reece et al, 2010) and stable relationship status (Ditekemena et al, 2012;Larsson et al, 2010;Morfaw et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…While research into whether ART reduces HIV stigma has proven contradictory or inconclusive (Maughan-Brown 2010, Campbell et al 2011b, Zuch andLurie 2011), the overwhelming response of the interview participants was that treatment, while not a guarantee to good health, had helped them live with the disease and cope with its negative social consequences. However, most participants still did not feel confident about disclosure, as exemplified in the reluctance to be observed taking ART medication in public.…”
Section: Discussionmentioning
confidence: 99%
“…Goffman's notion of social stigma -a key idea in the symbolic interactionist tradition within sociology -has been shown to be particularly useful for understanding the experiences of HIV-positive people in Southern Africa (Stein 2003, Visser et al 2009, Gilbert and Walker 2010, Campbell et al 2011b, Peltzer and Ramlagan 2011, Zuch and Lurie 2011. In his seminal text Stigma: Notes on the management of spoiled identity Goffman (1968) postulated that stigma is created when a person acquires an identity or attribute that a given society views as unacceptable.…”
Section: Stigma -The Origins and Contemporary Permutationsmentioning
confidence: 99%
See 1 more Smart Citation